World kidney forum: renal research in 19th century Germany - Ritz, Eberhard; Koleganova, Nadezda; Heidland, August (American journal of kidney diseases, 2010)
In the 19th century, clinical nephrology had not been established as a specific discipline of internal medicine, but major contributions to the understanding of renal physiology and kidney disease had been made by a number of authors from the German-speaking world. This essay describes the introduction of the concept of glomerular filtration by Carl Ludwig, the brilliant analysis of renal histology by Jacob Henle, the histologic description and insight into the evolution of chronic kidney disease by Friedrich Theodor von Frerichs, and the recognition of albuminuria in patients without primary kidney disease by Hermann Senator.